GE_GERICHTE C/13992/2016 vom 9. Juni 2017 - GE Cour de justice (2017)
MESURE PROVISIONNELLE ; OBLIGATION D'ENTRETIEN ; CONJOINT ; REVENU HYPOTHÉTIQUE ; REVENU ACCESSOIRE | CPC.276; CPC.317.1; CC.176.1.1;